An Analysis of Determinants of Corporate Financial Performance: Evidence from the Bucharest Stock Exchange Listed Companies - Georgeta Vintila; Elena Alexandra Nenu (International Journal of Economics and Financial Issues, 2015)
The purpose of this paper is to investigate potential factors of influence on corporate financial performance. The analysis was conducted on Romania's case and included a sample of 46 companies listed on the Bucharest Stock Exchange, within 2009-2013 period. In the first part of the analysis the companies have been classified using factor analysis and further, based on it, we have performed a cluster analysis using SAS program. Subsequently, selected variables were tested using multivariate regression models for unbalanced panel data. The results are contradictory regarding the impact of company size. Based on the accounting approach we obtained a positive impact determined by the number of employees, while based on the market approach, performance is negatively correlated with total assets. In terms of indebtedness a negative relationship was revealed. At the same time, the relationship regarding transparency and disclosure in reporting was not statistically validated.